IMPLEMENTASI KEBIJAKAN PELAYANAN PERIZINAN USAHA MIKRO KECIL BERBASIS OSS RBA DI KABUPATEN SITUBONDO PROVINSI JAWA TIMUR - Arwanto Harimas Ginting; Rizal Bahroni; Margaretha Rumbekwan (Jurnal Ilmiah Wahana Bhakti Praja, 2022)
This research aims to determine how the implementation of licensing policies for micro and small businesses based on the Online Single Submission Risk Based Approach (OSS RBA) in Situbondo Regency, East Java Province. This research is an implementation of the OSS RBA-based licensing policy based on the implementation Van Meter and Van Horn theory with 6 (six) indicators. This study uses a descriptive qualitative method with an inductive approach. Informants were determined by purposive sampling technique from the Office of Investment and One Stop Integrated Services, the Office of Cooperatives and Micro Enterprises in Situbondo Regency and business actors who had issued RBA OSS-based permits. Data condensation, data presentation and drawing conclusions were used as data analysis techiques. Observations, interviews and documentation were used as data collection. The research results show that the implementation of the RBA OSS-based micro and small business licensing service in Situbondo Regency based on the theory of implementing the Van Meter and Van Horn policies has been carried out quite well. This statement is based on the absence of significant problems with the implementation of policies and implementing agencies and business actors respond positively and strongly support the RBA OSS-based licensing policy.